American Immunity: War Crimes and the Limits of International Law - Patrick Hagopian (University of Massachusetts Press, 2013)
The history of international humanitarian law in the post–Second World War period is marked by two inconsistent—indeed, diametrically opposed—tendencies: first, the promulgation of universal standards of justice, the creation of institutions where they can be enforced, the advancing application of the principle of universal jurisdiction, and the global reach of the forces on which the enforcement of the law must rely; second, the capacity of the greatest of the great powers to achieve immunity from the application of those standards to itself and to its citizens.1 These two tendencies rest on the same set of conditions: the preponderance of U.S. military power, allowing it to serve in the role of the world’s policeman and hence to choose when and whether to subject its own citizens and troops to international law. For forty years in the second half of the twentieth century there was no U.S. jurisdiction in which veterans of the U.S. armed forces could be prosecuted for crimes they committed while in military service beyond the nation’s borders. During this period American troops could literally get away with murder as long as their crimes were not detected or were covered up until after they had separated from military service. This was not merely a theoretical possibility: some twenty former soldiers did, indeed, get away with murder. The jurisdictional problem was well known to the politicians who might have solved it: legislators were aware of the jurisdictional gap or jurisdictional void from the moment it opened up in 1955, when the U.S. Supreme Court struck down as unconstitutional Article 3(a) of the Uniform Code of Military Justice.2 This measure provided for the prosecution by court-martial of military veterans for crimes they committed outside the United States while in the armed forces. When the Supreme Court struck down that provision, Justice Hugo Black’s opinion for the court drew attention to a proposal that, because the judgment precluded military courts thereafter from trying veteran suspects for crimes committed while in uniform overseas, jurisdiction over such suspects should be vested instead in federal district courts. Accordingly, concerned members of Congress began to try to pass a law to achieve this purpose, and they and their successors continued to propose such bills periodically for the next forty years